A Study to Evaluate the Association of Varna in Healthy Individuals of Different Deha prakriti– An Observational Study - Yadav, Vandana; Bhojani, Meera K (International Research Journal of Ayurveda & Yoga, 2024)
Humans are given beauty as a heavenly gift. Throughout the beginning of time, its significance has been understood and valued, and attempts have been made to conserve and advance beauty in all of its forms. Some of the factors outlined in Ayurveda that play an important part in determining a person’s attractiveness include: (a) Prakriti, (b) Sara, (c) Samhanana, (d) Varna, (e) Prabha, and (f) Chhaya. These factors provide the aesthetic sense and essential basis of personality and beauty. Ayurvedic literature classifies seven types of Prakriti1 and characterized the skin color (Varna) on basis of Prakriti. There are many characters mentioned in Samhita for determination of Prakriti. Skin (Twacha) is one of criteria among them. This study has been undertaken to determine the association of prakriti and Varna.